Acute histological reactions in the otolith organs to inner ear drug delivery through a cochlear implant - Manrique-Huarte, Raquel; Álvarez de Linera-Alperi, Marta; Pérez-Fernández, Nicolás; Manrique, Manuel (Frontiers in Neurology, 2024)
Introduction Cochlear implantation is currently regarded as a safe and minimally invasive procedure. However, cochlear implantation can have an impact on vestibular function, despite the lack of correlation between patient symptomatology and damage in vestibular tests. Thus, the present study aims to analyze the presence of hydrops and histological reactions at the level of the vestibule after cochlear implantation with dexamethasone pump delivery in Macaca fascicularis (Mf). Materials and methods A detailed histological study was conducted on a total of 11 Mf. All 11 Mf were divided into three groups: 5 Mf were implanted with an electrode array HL-14 connected to a pump delivering FITC-dextran for 24 h (Group A); 4 Mf were implanted with a CI electrode array attached to a pump for FITC-dextran delivery for 7 days (Group B); and 2 Mf were considered the control group, without any kind of cochlear device implantation (Group C). After drug deliver, the selected macaques were euthanized to collect tissue samples for histological analysis. An experienced observer, focusing on the utricle and saccule areas, conducted a blinded inner ear histology analysis. Results Surgical procedures were successfully performed in all cases. No signs of cochlear reaction to the device were observed, including neither collapse nor fibrosis. Endolymphatic sinus dilatation was observed in Mf4A and Mf3B, while cochlear hydrops was observed in Mf3A. The mean areas of the utricle and saccule exhibited some statistically significant differences, specifically, in the saccule between groups C and both groups A (p = 0.028) and B (p = 0.029); however, no significant differences were observed between groups A and B or among comparisons of the utricle. Discussion A significant concern relates to the safety of cochlear implantation with regard to vestibular preservation and hearing. New advancements in electrode arrays, such as CI devices coupled with delivery pumps, pose a challenge in maintaining minimally traumatic surgical concept-based procedures without affecting the inner ear homeostasis. The implantation of this device may cause vestibular hydrops in the saccule, indicating that the longer the time of substance release, the greater the grade of hydrops evidenced at the saccular level. Apart from this finding, the risk of histological damage to the vestibule is low.